On the role of cell surface associated, mucin‐like glycoproteins in the pennate diatom Craspedostauros australis (Bacillariophyceae). Issue 1 (28th October 2022) - Poulsen, Nicole; Hennig, Helene; Geyer, Veikko F.; Diez, Stefan; Wetherbee, Richard; Fitz‐Gibbon, Sorel; Pellegrini, Matteo; Kröger, Nils
Abstract : Diatoms are single‐celled microalgae with silica‐based cell walls (frustules) that are abundantly present in aquatic habitats, and form the basis of the food chain in many ecosystems. Many benthic diatoms have the remarkable ability to glide on all natural or man‐made underwater surfaces using a carbohydrate‐ and protein‐based adhesive to generate traction. Previously, three glycoproteins, termed FACs (F rustule A ssociated C omponents), have been identified from the common fouling diatom Craspedostauros australis and were implicated in surface adhesion through inhibition studies with a glycan‐specific antibody. The polypeptide sequences of FACs remained unknown, and it was unresolved whether the FAC glycoproteins are indeed involved in adhesion, or whether this is achieved by different components sharing the same glycan epitope with FACs. Here we have determined the polypeptide sequences of FACs using peptide mapping by LC–MS/MS. Unexpectedly, FACs share the same polypeptide backbone (termed CaFAP1), which has a domain structure of alternating Cys‐rich and Pro‐Thr/Ser‐rich regions reminiscent of the gel‐forming mucins. By developing a genetic transformation system for C. australis, we were able to directly investigate the function of CaFAP1‐based glycoproteins in vivo. GFP‐tagging of CaFAP1 revealed that it constitutes a coat around all parts of the frustule and is not an integral component of the adhesive. CaFAP1‐GFP producing transformants exhibited the same properties as wild type cells regarding surface adhesion and motility speed. Our results demonstrate that FAC glycoproteins are not involved in adhesion and motility, but might rather act as a lubricant to prevent fouling of the diatom surface.